Carbon Emission Disclosure in Indonesia's Energy Sector: The Role of Environmental Performance and Media Exposure - Nurjanah, Tria Siti; Mulyandini, Vita Citra (Jurnal Akuntansi, 2024)
Abstract Purpose - This study examines the effect of environmental performance and media exposure on carbon emission disclosure. Design/methodology/approach - The research method used is quantitative with data collection techniques through literature study and documentation. The population used in this study is energy sector companies listed on the Indonesia Stock Exchange in 2018-2022. The sampling technique used purposive sampling, and a sample of 9 companies was obtained so that the total sample was 45 data. The analysis techniques used in this research are the classical assumption test, multiple linear regression, correlation test, determination, t-test, and f-test using SPSS version 25. Findings - Research shows that environmental performance and media exposure has no effect on carbon emission disclosure.Research limitations/implications - The time constraint of this research may also complicate monitoring changes in carbon disclosure over time. Keywords: Environmental Performance, Media Exposure, and Carbon Emission Disclosure